Manajemen Fisioterapi pada Pasien Carpal Tunnel Syndrome Dengan Kombinasi Nerve Gliding Exercise dan Modalitas Elektroterapi di RSJ Soerodjo Magelang: case report - Muh. Ghozy Rezki Ramadan Sitompul; Umi Budi Rahayu; Dyah Wahyu Utami (Pusat Riset dan Inovasi Nasional, 2026)
Background: Carpal Tunnel Syndrome (CTS) is a condition caused by compression of the median nerve at the wrist, resulting in pain, paresthesia, and decreased hand function. This condition is commonly experienced by individuals who perform repetitive wrist activities. Objective: To determine the effectiveness of a combination of neural mobilization exercises and electrotherapy modalities in improving hand function, increasing muscle strength, and reducing pain in a patient with Carpal Tunnel Syndrome. Methods: This study used a case report design involving a 57-year-old female patient (Mrs. Q) who presented with pain and sensory disturbances in the right hand. The intervention was administered for four weeks and consisted of ultrasound therapy, Transcutaneous Electrical Nerve Stimulation (TENS), grip strengthening exercises, and nerve gliding exercises. Outcome measures included pain intensity assessed using the Numeric Rating Scale (NRS), muscle strength evaluated using Manual Muscle Testing (MMT), and functional ability measured using the Wrist Hand Disability Index (WHDI). Results: The evaluation showed a reduction in pain intensity, with resting pain at 0/10, tenderness at 4/10, and movement pain at 4/10. Muscle strength improved from grade 3 to grade 4 based on MMT. Functional ability also improved, as indicated by a 20% reduction in the WHDI score. The combination of these interventions proved effective as a conservative management approach for Carpal Tunnel Syndrome. Conclusion: The administration of ultrasound, TENS, grip strengthening exercises, and nerve gliding exercises over four therapy sessions in Mrs. Q resulted in decreased pain, increased muscle strength, and improved hand functional ability.